Rationality Metamorphoses in Context of Culture - E. S. Logovaya (Наука и техника)
The classical rationality interprets the world as a stable and self-prosperous existence. While determining structural invariants of existence the given form of rationality proceeds from ideal concepts of proportionality, predetermination and self-identity as basic methods for Universum description. Non-classical rationality is oriented to investigation of self-developing systems that presuppose the necessity to introduce such concepts as «non-identity», «unpredictability», «opportunity», «interactivity» in research matrix.